ANALISIS PRAKTIK DZIKIR UNTUK MENGATASI KECEMASAN SANTRI PONDOK DARUT TAUHID PESANTREN ZAINUL HASAN GENGGONG - Ockta, Latifah; Qudni, Abu Yazid Adnan; Lestari, Puput (Jurnal Al-Fatih, 2025)
Anxiety is a common psychological issue experienced by students (santri), particularly during their adaptation to the disciplined environment and routines of Islamic boarding schools (pesantren). This study aims to analyze the role of dzikir (Islamic remembrance) as a religious coping strategy to reduce anxiety among santri at Pondok Darut Tauhid, Zainul Hasan Genggong Islamic Boarding School. A qualitative approach with a case study method was employed. Data were collected through observation, in-depth interviews, and documentation of selected students who regularly practice dzikir. The findings indicate that consistent dzikir practices—both individually and in groups—contribute to emotional calmness, increased spiritual awareness, and greater mental resilience. Dzikir also helps shift the students’ focus away from negative thoughts that often trigger anxiety. Thus, dzikir serves not only as a religious ritual but also as an effective coping mechanism for maintaining students’ mental well-being within the pesantren setting. The study recommends strengthening the culture of dzikir as part of mental and spiritual development programs in Islamic boarding schools.